Endocrinology Telehealth Consultation Improved Glycemic Control Similar to Face-to-Face Visits in Veterans. (September 2016) - Liu, Winnie; Saxon, David R.; McNair, Bryan; Sanagorski, Rebecca; Rasouli, Neda
Background: Rates of diabetes for veterans who receive health care through the Veterans Health Administration are higher than rates in the general population. Furthermore, many veterans live in rural locations, far from Veterans Affairs (VA) hospitals, thus limiting their ability to readily seek face-to-face endocrinology care for diabetes. Telehealth (TH) technologies present an opportunity to improve access to specialty diabetes care for such patients; however, there is a lack of evidence regarding the ability of TH to improve glycemic control in comparison to traditional face-to-face consultations. Methods: This was a retrospective cohort study of all new endocrinology diabetes consultations at the Denver VA Medical Center over a 1-year period. Results: A total of 189 patients were included in the analysis. In all, 85 patients had received face-to-face (FTF) endocrinology consultation for diabetes and 104 patients had received TH consultation. Subjects were mostly males (94.7%) and the mean age was 62.8 ± 10.1 years old. HbA1c improved from 9.76% (9.40% to 10.11%) to 8.55% (8.20% to 8.91%) ( P < .0001) for the TH group and from 9.56% (9.16% to 9.95%) to 8.62% (8.22% to 9.01%) ( P < .0001) for the FTF group after 1 visit. This change in HbA1c was not significantly different in the TH and FTF groups ( P = .24). TH visits were associated with a hypothetical savings in median distance traveled of 231.2 miles per trip (which equates to 94.79 saved per trip). Conclusions: Endocrinology TH consultations improved short-term glycemic control as effectively as traditional FTF visits in a veteran population with diabetes.